2023
DOI: 10.3389/fenvs.2023.1101745
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of biomass burning in Southeast Asia on aerosols over the low-latitude plateau in China: An analysis of a typical pollution event

Abstract: From March to April, widespread forest fires and agro-residue burning frequently occur in Southeast Asia, which release large amounts of gas species and aerosols and impact air quality over the wide source and downwind regions. In this study, we investigated the impact of biomass burning (BB) over Southeast Asia on particulate matter concentrations and aerosol properties in downwind areas of the low-latitude plateau from 1 March to 30 April 2019, with a focus on a typical pollution event in Kunming (KM), the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Additionally, Yin (2020) discovered that over the past 18 years (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018), the PSEA region predominantly experienced the peak of BB activity in March each year. Fan et al (2023) and Duc et al (2021) confirmed that the PSEA suffered severe air quality impacts during the BB in March 2019. Therefore, centered on the period of March 2019, this study aims to analyze how emission uncertainties or differences from different BB inventories affect the spatial and temporal distribution of aerosols and their radiative effects in the PSEA region.…”
Section: Introductionmentioning
confidence: 69%
“…Additionally, Yin (2020) discovered that over the past 18 years (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018), the PSEA region predominantly experienced the peak of BB activity in March each year. Fan et al (2023) and Duc et al (2021) confirmed that the PSEA suffered severe air quality impacts during the BB in March 2019. Therefore, centered on the period of March 2019, this study aims to analyze how emission uncertainties or differences from different BB inventories affect the spatial and temporal distribution of aerosols and their radiative effects in the PSEA region.…”
Section: Introductionmentioning
confidence: 69%
“…Thepnuan et al [14] claim that during dry season haze episodes in upper Southeast Asia, forest and agri-waste burning are major contributors to the aerosols. Fan et al [15] found, in a study looking at biomass burning during pollution events in Southeast Asia and how they impact aerosol distribution over the low-latitude plateau in China, that 59.5% of PM 2.5 mass produced by biomass burning was sourced from the Myanmar-Thailand border. Yin et al [16] found in a study investigating air pollution in mainland Southeast Asia from 2001 to 2016 that the variation of air quality is closely related to local biomass burning, and the latter contributed more than human activities to PM 2.5 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al. (2023) investigated the impacts of BB over Southeast Asia on atmospheric aerosol concentrations and properties in the Yunnan‐Guizhou Plateau in spring 2019 by using a wide variety of observations, as well as numerical simulations, and indicated that the transported BB pollutants from Southeast Asia could increase the daily mean PM 2.5 , PM 1 , and black carbon concentrations by 78%∼83% in Kunming, the capital of Yunnan Province. Notably, the CO 2 could also be transported to China like other BB pollutants (e.g., PM 2.5 ) and have a non‐negligible effect on the atmospheric CO 2 concentration in South China.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2020) analyzed the variations in observed PM 2.5 concentrations at monitoring stations in Yunnan (a province bordering Southeast Asia in Southwest China) during February 2013-December 2018 and pointed out that the pollutant concentrations generally displayed sharp increases and rapid decreases, consisting with the pollution transport characteristics. Fan et al (2023) investigated the impacts of BB over Southeast Asia on atmospheric aerosol concentrations and properties in the Yunnan-Guizhou Plateau in spring 2019 by using a wide variety of observations, as well as numerical simulations, and indicated that the transported BB pollutants from Southeast Asia could increase the daily mean PM 2.5 , PM 1 , and black carbon concentrations by 78%∼83% in Kunming, the capital of Yunnan Province. Notably, the CO 2 could also be transported to China like other BB pollutants (e.g., PM 2.5 ) and have a non-negligible effect on the atmospheric CO 2 concentration in South China.…”
mentioning
confidence: 99%